Let A = ( − 1 3 2 4 ) .
Express A 6 = α A + β I ; where I is the identity matrix.
Calculate α + β .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I guess it is easy to just square the matrix since it is 2x2. I essentially did the same thing, except I used the characteristic polynomial and the Cayley-Hamilton Theorem to arrive at A 2 = 3 A + 1 0 I . This method will extend to larger matrices as well without any guessing for coefficients.
I think this is the best process and can be extended to higher powers also. But I think, we need not find all the remaining powers. We can directly square A³ to get at the desired result. Marked as Brilliant!!!!
A more general approach to this problem is using the Cayley-Hamilton Theorem .
The characteristic polynomial for A is p ( λ ) = d e t ( A − λ I ) = ( − 1 − λ ) ( 4 − λ ) − 6 = λ 2 − 3 λ − 1 0
Applying Cayley-Hamilton, we have p ( A ) = A 2 − 3 A − 1 0 I = 0 , which can be rearranged to A 2 = 3 A + 1 0 I
By the repeated process of multiplying both sides by A and substituting A 2 = 3 + 1 0 I , we eventually find α and β :
A 3 = ( 3 A + 1 0 I ) A
= 3 A 2 + 1 0 A
= 3 ( 3 A + 1 0 I ) + 1 0 A
= 1 9 A + 3 0 I
Similarly, A 4 = 1 9 ( 3 A + 1 0 I ) + 3 0 A = 8 7 A + 1 9 0 I , A 5 = 8 7 ( 3 A + 1 0 I ) + 1 9 0 A = 4 5 1 A + 8 7 0 I , and A 6 = 4 5 1 ( 3 A + 1 0 I ) + 8 7 0 A = 2 2 2 3 A + 4 5 1 0 I
Therefore, α = 2 2 2 3 and β = 4 5 1 0 , so α + β = 6 7 3 3
A very simple way to do this is to consider an eigenvector of A call it V, with eigenvalue x. The characteristic poly of A is x^2-3x-10. So the eigenvalues are 5 and -2. Now we know A^6 V= aAV+bIV. Now since V is an eigenvector with eigenvalue x we have A^6V=x^6V and AV=xV. So we have an equation x^6V=axV+bV. When we factor out V we get (x^6)V=(ax+b)V. So we have x^6=ax+b we sub in 5 and -2 and get two linear equations which we solve to get a+b=6733.
Rewrite the equation as: A 6 − α A = β I And calculate the values: [ 2 2 8 7 + α 6 6 6 9 − 3 α 4 4 4 6 − 2 α 1 3 4 0 2 − 4 α ] = [ β 0 0 β ]
That leads to: α = 2 2 2 3 ; β = 4 5 1 0
How did you arrive at your matrix so easily? What did you do?
Log in to reply
i used this
https://www.mathsisfun.com/algebra/matrix-calculator.html
Problem Loading...
Note Loading...
Set Loading...
A shorter method would be to write A 2 = m A + n I .
Then find A 2 by simple multiplication and equate it to m A + n I to find m = 3 n = 1 0 .
Now write A 3 = A ( A 2 ) = A ( 3 A + 1 0 I ) = 1 9 A + 3 0 I .
Similarly find remaining powers of A as above while substituting A 2 every time with 3 A + 1 0 I to finally arrive at A 6 = 2 2 2 3 A + 4 5 1 0 I . So α = 2 2 2 3 β = 4 5 1 0 and α + β = 6 7 3 3 .
NOTE: This solution still may not provide the best process yet